PENGUJIAN DEBT FINANCED DIVIDEND PADA PENGARUH KEBIJAKAN UTANG TERHADAP KEBIJAKAN DIVIDEN DAN KEPUTUSAN INVESTASI - Stevani Putri Kurnia; Putu Anom Mahadwartha; Mudji Utami (Jurnal Manajemen, 2015)
This study analyzes the effect of debt policy on dividend policy and investment decision on corporate manufacturing industry sector in IDX the period of 2009-2013. This study uses a quantitative approach to multiple linear regression analysis model. This study uses a sample of firms / companies who are in the manufacturing industry sectors in IDX period of 2009-2013. This study finds that debt policy doesn’t have significant effect on dividend policy, while control variable, MBVE has negative significant effect on dividend policy. Debt policy has positive significant effect on investment decision while MBVE doesn’t have significant effect on investment decision on manufacturing industry sector in IDX the period of 2009-2013.